Pecularities of nanoparticle reflection from a barrier - Ratner, M.A.; Tur, A.V.; Yanovsky, V.V. (Functional Materials, 2013)
This work is devoted to molecular dynamics modelling of collision of nanoparticle having a small number of degrees of freedom with a structureless plain. It is established that velocity of nanoparticle after collision can exceed the initial one. The main system parameters, which determine nanoparticle behavior, are established.